Alquimia da fé: o poder transformador do turismo religioso - (:unkn) unknown (Universidade Federal do Pampa, 2022)
The present article has as its objective to sintetize the production and the publishing of a non-fiction hipertextual multimedia book approaching stories about two catholic touristic routes at the region of Vale do Paraíba, at São Paulo’s (the brazilian state) countryside. The non-fiction book, entitled “Alquimia da Fé: o Poder Transformador do Turismo Religioso”, which translates to English as “Alchemy of Faith: the Transforming Power of Religious Tourism”, is a product planned from the idea of aggregating stories about the self-knowledge brought by the contact of followers of the Roman Apostolic Catholic Church with religious symbols, temples and touristic routes. Contact which was prohibited by the pandemic context of 2020 and 2021, when restrictions were made to the touristic activity as a whole. Thinking about the gradual flexibilization of restrictive measures, mainly about the focus of the book, São Paulo’s countryside, the product brings deep researched reports about how people connect with fait, comprehend theirs personality and change (in social, economic, politics and other aspects) by the means of catholic pilgrimages, visitation of temples or administration of religious centers. The non-fiction book is published through the platform Issuu and possesses hipertextual and multimedia functions, which requires the interaction of the reader to approach and comprehend the reading. Besides, the book has the digital resource of hypertextuality, which, trough links, turns it able to the reader to access other journalistic, scientific or/and verified information in general. The product is able to be read and accessed through the link: .
Keywords: Turismo - Aspectos religiosos; Fé; Religião; Religiosidade; Turismo – São Paulo; Tourism - Religious aspects; Faith; CNPQ::CIENCIAS SOCIAIS APLICADAS